Traversing boundaries: thrombus in transit with paradoxical embolism - Varun Miriyala; Muhammad Umer Awan; Kirmanj Faraj; Bipinpreet Nagra (Greater Baltimore Medical Center, 2016)
A 72-year-old male is diagnosed with paradoxical embolus after he presented with concurrent deep vein thrombosis, stroke, and multiple arterial emboli in the presence of a patent foramen ovale (PFO). Paradoxical embolus requires the passage of a thrombus from the venous into the arterial circulation through a right-to-left shunt leading to systemic embolism. But, despite the high incidence of PFO (27.3% across all age groups by autopsy), paradoxical embolism (PDE) is uncommon, representing <2% of all arterial emboli. We present a case report where a thrombus has been directly observed passing through the PFO during an echocardiogram study; thus, clearly delineating the true cause of multiple thromboemboli and stoke in our patient. Subsequent Transesophageal Echocardiography (TEE) also interestingly showed the thrombus in transit in the aorta and pulmonary artery.